Health in Algorithmic Terms: A Walkthrough Exploration of Medical App - Padricelli, Giuseppe Michele; Crescentini, Noemi; Acampa, Suania (Italian Sociological Review, 2024)
This wide range of health-related theories often makes use of algorithms as tools to support diagnoses and the identification of optimal care and well-being pathways. Medical platforms, the algorithms that characterize them, and the digital devices needed to overlap/integrate the digital environment with everyday spaces allow for collecting, sharing, and storing health and well-being data (Lupton, 2015). In the case of TonicApp, a medical device that, in its presentation, recognizes and guarantees the technical and scientific safety of its diagnostic algorithms; data are generated and stored directly by healthcare professionals, who are accompanied by other types of professionals, such as engineers responsible for algorithmic transposition. How is the algorithmic intervention configured to create and administer medical diagnoses? What is the level of trust of medical personnel in these platforms, and how does the use of these platforms change the practice of medicine and the doctor-patient relationship? These research questions guide the work in adopting a mixed-digital research design with a sequential-exploratory approach. These questions invite an initial exploration of the context, structure, and environments of TonicApp in Italy. The Walkthrough approach (Light, Burgess, and Duguay, 2018; Decuypere, 2019) allows for direct interaction with the TonicApp interface to identify, select, and dissect the technological mechanisms it comprises and define any cultural references that icons and interfaces may incorporate. Following this initial exploratory phase, an in-depth immersion phase will be prepared through a series of semi-structured interviews with the doctor-users of TonicApp to shed light on the platform’s usage patterns and how this tool has contributed to changes in the practice of medicine and the relationship with patients.